Gut cannabinoid receptor 1 regulates alcohol binge-induced intestinal permeability - Bin Gao; Luca Maccioni; George Kunos; Szabolcs Dvorácskó; Grzegorz Godlewski; Resat Cinar; Malliga R Iyer (eGastroenterology)
Background Endocannabinoids acting via cannabinoid receptor 1 (CB1R) can elicit increased intestinal permeability (a condition also called ‘leaky gut’). Alcohol binge can adversely affect digestive functions, including intestinal permeability; however, the underlying mechanisms remain incompletely understood. The current study aimed at examining whether CB1R is involved in alcohol binge-induced intestinal permeability.Methods We developed intestinal epithelial-specific CB1R knockout (CB1IEC−/−) mice and evaluated the in vivo contribution of gut CB1R in alcohol binge-induced intestinal permeability.Results Alcohol binge increased anandamide levels in the proximal small intestine in association with increased intestinal permeability. Radioligand binding and functional assays confirmed that the genetic deletion of intestinal epithelial CB1R did not alter the density or functionality of CB1R in the brain. Additionally, a peripheral CB1R antagonist, (S)-MRI-1891 (INV-202/monlunabant), exhibited comparable binding affinity to CB1R in brain homogenates. An acute oral administration of (S)-MRI-1891 (3 mg/kg) reduced alcohol binge-induced intestinal permeability in littermate control CB1f/f (CB1 floxed/floxed) mice but had no effect in CB1IEC−/− mice, underscoring the role of intestinal CB1R in this phenomenon. Mechanistically, we found that alcohol activated intestinal epithelial CB1R-ERK1/2 pathway with subsequent downregulation of tight junction proteins and reduction in villi length. In addition, targeting intestinal CB1R and downstream ERK1/2 was able to reverse this process, with subsequent upregulation of tight junction proteins and increased villi length, thus improving gut barrier function. Despite the effects on intestinal permeability, deletion of intestinal CB1R did not significantly affect metabolic parameters and liver disease.Conclusion Our findings suggest that alcohol promotes leaky gut via the activation of gut epithelial CB1R and demonstrate that inhibition of CB1R with peripheral-restricted selective CB1R antagonists can prevent alcohol binge-induced intestinal permeability.